(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: urinary TNT, King’s score and liver fibrosis in patients with chronic hepatitis caused by occupational TNT poisoning. Methods: 177 patients were diagnosed with chronic hepatitis due to occupational exposure to TNT; descriptive cross-sectional study; whole sample collection: biopsy for histopathology; liver degeneration stage according to Metavir; King’s score. Results: Patients in group F0 (55.9%), F1 (36.2%), and F2 (7.9%) showed (61.0%) had TNT detected in their urine. The group without significant liver fibrosis had 97 patients with urinary TNT (59.5%), lower than the group with significant liver fibrosis (78.6%). The F2 group with liver fibrosis had the highest King’s score (5.36 ± 1.68), while the F0 group had the lowest (4.69 ± 1.09). The average King score increased progressively from F0 to F1 to F2. The King’s score in the group with liver fibrosis (4.86 ± 1.50) was higher than in the group without liver fibrosis (4.69 ± 1.09). The King score in the group with significant liver fibrosis (5.36 ± 1.68) was higher than in the group without significant liver fibrosis (4.71 ± 1.24). Conclusion: TNT in urine was present in 61% of cases. In the group without significant liver fibrosis, 97 patients had lower levels of TNT in urine (59.5%) compared to the group with significant liver fibrosis (78.6%). The average King score increases progressively from F0, F1, to F2; group F≥1 (4.86 ± 1.50) is higher than in F0 (4.69 ± 1.09), p=0.478. In group F≥2 (5.36 ± 1.68), the King score is higher than in F<2 (4.71 ± 1.24), p=0.144.